The Expression of CD38 ADP-ribosyl Cyclase Ectoenzyme in Immune Cells of Cardiac Surgical Patients - Martina Koláčková; Manuela Trojáčková Kudlová; Vladimír Lonský; Jiří Manďák; Pavel Kuneš; Karolína Jankovičová; Dana Vlášková; Ctirad Andrýs; Jan Krejsek (Acta Medica, 2008)
Background: This study was aimed at following the changes in the expression of CD38 ADP-ribosyl cyclase ectoenzyme on peripheral blood immune cells of patients undergoing cardiac surgical operations. Patients and Methods: The expression of CD38 on lymphoid and myeloid cells was determined by immunofluorescence and flow cytometry in forty cardiac surgical patients assigned to surgery either using (“on-pump”, n=20) or without the use (“off-pump”, n=20) of cardiopulmonary bypass. Results: There was a very rapid upregulation of CD38 expression in “on-pump” patients, becoming significant at declamping of aorta (p<0.01) for myeloid cells and at the weaning from CPB (p<0.001) for lymphocytes. The increased expression of CD38 on lymphocytes in “off-pump” patients was prolonged for the entire observation period. However, significant differences in the expression of CD38 between “on-pump” and “off-pump” patients were not found either in lymphoid or myeloid cells. Conclusion: CD38 expression in immune cells of cardiac surgical patients is upregulated early during surgery, providing additional activation stimuli to the cell substrate of the inflammatory response induced by cardiac surgery.